Wild Persistence : Poems - Hooper, Patricia, 1941- (Book collections on Project MUSE., 2019)
The poems in WILD PERSISTENCE often involve moments when the human and natural worlds intersect: a Sandhill Crane dancing at the window of a grieving woman, a copperhead snake confronting a gardener, a billboard photo of a missing child slowly being eroded by weather and the passage of time. Although these poems mourn numerous losses, they celebrate the world in which such losses take place, turning for perspective to nature with its cyclical renewals and to the resilience of the human spirit.